(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
A conceptualization of the object "meaningful task in/for the initial professional training of mathematics teachers" is presented. Regarding the methodological route followed, first, tasks designed by the members of the research team, in their role as mathematics teacher trainers, implemented at different times in a course of Didactics of Arithmetic and Algebra, were collected in order to recognize empirically the characteristics of meaningful tasks. Next, a documentary review was carried out to locate theoretical references that addressed, on the one hand, the concept of task in the framework of teacher training and, on the other hand, the meaning of meaning in mathematics teacher training. From this review, and its contrast with the initial characteristics, the proposed conceptualization is derived and the conclusions presented regarding the importance of focusing on the tasks proposed to future educators.